CONSUMER CULTURE AMONG SOCIOLOGY STUDENTS OF GORONTALO STATE UNIVERSITY - Moobiato, Sri Anggriani; Olii, Risti; Karim, Titan; Ramadhani, Vanya Dyah Pitaloka Maharani A.C. (Academic Solution Publisher, 2025)
This study explores consumer culture among Sociology students at Gorontalo State University, focusing on the forms, driving factors, meanings, symbolic interactions, and social impacts of consumer behavior. The research approach used was qualitative, with data collected through in-depth interviews with eight students from various semesters and classes from October 27 to November 30, 2025. The findings indicate that consumer behavior primarily occurs in the purchase of non-essential goods, such as clothing, gadgets, and lifestyle products, influenced by peer pressure, social media trends, and family background. Internal factors such as personal financial awareness and family values, as well as external factors such as social media exposure and peer influence, collectively shape student consumption patterns. Consumption serves not only to fulfill needs but also as a symbol of self-expression, identity construction, and social integration. Symbolic interactions influence students' perceptions of needs and wants, guiding consumption decision-making in a social context. The socio-impacts of consumer culture include status competition, financial pressure, and social inequality, while fostering creativity and social bonds.